Actividad antimicrobiana de cascarilla de cinco variedades de Coffea arábica (café) frente a agentes patógenos. - Honores Jiménez, Michael Fernando; Zambrano Murillo, Ambar Nicole (My University, 2025)
The present study evaluated the antimicrobial activity of shell extracts of five varieties of Coffea arabica (Yellow Catuaí, Red Catuaí, Acawa, Sarchimor and San Salvador) against bacterial and pathogenic fungal strains. Microdilution techniques were used to determine the minimum inhibitory concentration (CMI) and minimum bactericidal concentration (CMB), as well as spectrophotometry to measure optical density. The results showed that the Acawa and Sarchimor varieties showed greater antimicrobial activity, especially against Staphylococcus aureus and Pseudomonas aeruginosa, while yellow Catuaí was the least effective. Likewise, through solid media tests, the inhibition of the growth of filamentous fungi such as Trichoderma viride and Fusarium spp. was evidenced, which reinforces the potential of these extracts as natural antimicrobial agents. The variability in effectiveness was associated with differences in the concentration of bioactive compounds such as phenolic compounds, caffeine and tannins, which affect the integrity of microbial membranes and their metabolism. These findings underline the value of the coffee husk as an alternative resource for the development of sustainable pharmaceutical products and contribute to the revaluation of agro-industrial waste. In addition, the research shows the importance of implementing new strategies for the use of coffee by-products, contributing both to innovation in the area of phytopharmacicals and to the reduction of the environmental impact generated by organic waste.
El presente estudio evaluó la actividad antimicrobiana de extractos de cascarilla de cinco variedades de Coffea arabica (Catuaí rojo, Acawa, Sarchimor,Catuaí amarillo y San Salvador) frente a cepas bacterianas y fúngicas patógenas. Se utilizaron técnicas de microdilución con el fin de determinar la concentración mínima inhibitoria (CMI) y concentración mínima bactericida (CMB), así como espectrofotometría para medir la densidad óptica. Los resultados demostraron que las variedades Acawa y Sarchimor presentaron mayor actividad antimicrobiana, especialmente contra Staphylococcus aureus y Pseudomonas aeruginosa, mientras que Catuaí amarillo fue la menos efectiva. Asimismo, mediante ensayos en medio sólido se evidenció la inhibición del crecimiento de hongos filamentosos como Trichoderma viride y Fusarium spp., lo cual refuerza el potencial de estos extractos como agentes antimicrobianos naturales. La variabilidad en la efectividad se asoció a diferencias en la concentración de compuestos bioactivos como compuestos fenólicos, cafeína y taninos, los cuales afectan la integridad de las membranas microbianas y su metabolismo. Estos hallazgos subrayan el valor de la cascarilla de café como un recurso alternativo para el desarrollo de productos farmacéuticos sostenibles y contribuyen a la revalorización de residuos agroindustriales. Además, la investigación evidencia la importancia de implementar nuevas estrategias de aprovechamiento de subproductos del café, contribuyendo tanto a la innovación en el área de fitofármacos como a la reducción del impacto ambiental generado por residuos orgánicos.
Keywords: CMB; CMI; ACTIVIDAD ANTIMICROBIANA; CONCENTRACIÓN